Tuberculinización en bovinos en el Valle de Balsillas (Caquetá) (1992)
The main purpose of this Study was to asses the sanitary situation dealing with bovine tuberculosis in the Balsillas Valley, a region with previous referenced disease. All the bovines with six weeks of age were tested one by one in each farm from this geografical area. The study was iniciated in July, 1987 and up to now 17.612 animals have been tested with 623 positive reactors to PPD. All infected animals were killed and Mcohaeieriu,n boris was isolated from lymph nodes from seven animals. A series of sanitary measures were taken in order to control the disease. These preventive measures have demostrated to be effective and initial prevalence of 9.82% in 1987 decreased to 1 .05% in 1990. We recommend to continue such activities in order to avoid the transmission of tuberculosis to farms uninfected areas and to minimize the possibility of reinfection to cleaned farms. We note that it is important to prevent the transmission of tuberculosisi to other animal species including the man.